'Between a rock and a hard place': Challenging encounters between disability service clients and workers. Issue 4 (2nd October 2021) - Nykänen, Hanna
ABSTRACT: Professional relationships in the health and welfare sector involve many challenging client encounters. This study aims to describe what kind of client interaction social service workers in disability services find challenging and how they rationalise and manage these challenges. The study investigates disability service workers' perceptions of challenging client interactions using data from 22 interviews with disability service workers in two hospital districts. Interviewees highlighted lack of mutual trust and lack of shared understanding as two issues arising in challenging communicative behaviours that disability service workers find burdensome and miserable. The interviewees' accounts referred to four aspects of these challenges: 1) individual, 2) third-party, 3) structural and 4) experiential. In addition, six different management strategies were identified: 1) adjusting interaction, 2) listening, 3) negotiating, 4) problem solving, 5) withdrawing and 6) encounter interruption.